STUDI TENTANG MINAT BACA MAHASISWA FAKULTAS ILMU PENDIDIKAN UNY - Hardianto, Deni (MAJALAH ILMIAH PEMBELAJARAN, 2011)
Reading books is one of the effective learning activities in acquiring science and knowledge, but nowadays, the students reading interest is getting lower. This research goals are: (1) describes the portrait of FIP UNY students, related to reading interests. (2) describes the FIP UNY students supporting and blocking factors in reading. This research uses the survey quantitative approach. The subjects are FIP UNY students. This research uses a questionnaires, observation, and interviews for the data collection method, and being analyzed using descriptive analysis, tabulation of frequencies and percentages. From this research found: (1) the students reading interests, is generally included in the low category, (2) the most students activities in campus is just waiting in front of the class, only a small amount of students who use the free time to read a book or to visit the library. (3)FIP students prefer to read a popular, scientific book. They don't interested in a scientific book, because of the non attractive layout and design , (4) the students time to spent in reading the book is relatively low, less than 1 hour every day, and in some cases, they never read except for the examinations, (5) the most students blocking factors in reading, comes from the student itself, that shown in their low reading habits or hobbies.